Accelerating the design of highly separable Fe‐containing intermetallics in Al–Si alloys via DFT calculations and experimental validation - Xiaozu Zhang; Dongtao Wang; Hiromi Nagaumi; Rui Wang; Zibin Wu; Minghe Zhang; Dongsheng Gao; Hao Chen; Pengfei Wang; Pengfei Zhou; Yunxuan Zhou; Zhixiu Wang; et al. (Materials Genome Engineering Advances, 2025)
Abstract The detrimental Fe element in Al‐Si cast alloy can be effectively removed by Fe‐containing intermetallics separation. However, the formation temperature of Fe‐containing intermetallics can be further improved to increase the removal efficiency of Fe element. The effects of the Cr/Mn atomic ratio on the stability, theoretical melting point, elastic modulus, and thermal properties were calculated with the aim of improving the stability of the α‐Al(FeMnCr)Si phase. An increased Cr/Mn atomic ratio effectively increased the stability, theoretical melting point, elastic modulus, isobaric heat capacity, and reduced the volumetric thermal expansion coefficient of α‐Al(FeMnCr)Si phase, which can be explained by the strengthened Al‐Cr and Si‐Cr chemical bonds. The experimental study results revealed that the formation temperature and Young's modulus of the α‐Al(FeMnCr)Si phase increase from 673.0°C and 228.5 GPa to 732.0°C and 272.1 GPa with the Cr/Mn atomic ratio increasing from 0.11 to 0.8, which better validates the thermodynamic stability, theoretical melting point and elastic modulus calculation results. These results provide a new strategy for designing Fe‐containing intermetallics with the desired properties, which contributes to guiding the development of high‐performance recycled Al‐Si alloys.